2009
DOI: 10.1509/jmkg.73.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity and the Service-Profit Chain

Abstract: The IMU offers the following services and expertise: Management Know-HowThe IMU publishes papers geared towards managers in companies. Subjects highly relevant to business practice are presented here in a compact and concise manner, and scientific research results are efficiently communicated. In many cases, these publications are based on application-oriented research and cooperation projects involving a large number of global companies. Scientific Working PapersThe scientific studies conducted by the IMU ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
492
3
9

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 558 publications
(520 citation statements)
references
References 131 publications
16
492
3
9
Order By: Relevance
“…Customer-company identification (CCID) is an affective and sociological foundation for developing enduring customer-company relationships and customer loyalty (Bagozzi, Bergami, Marzocchi, & Morandin, 2012;Homburg, Wieseke, & Hoyer, 2009). As external stakeholders, customers build attachments and identify with companies through multiple interactions (Hughes & Ahearne, 2010;Lam, Ahearne, Hu, & Schillewaert, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Customer-company identification (CCID) is an affective and sociological foundation for developing enduring customer-company relationships and customer loyalty (Bagozzi, Bergami, Marzocchi, & Morandin, 2012;Homburg, Wieseke, & Hoyer, 2009). As external stakeholders, customers build attachments and identify with companies through multiple interactions (Hughes & Ahearne, 2010;Lam, Ahearne, Hu, & Schillewaert, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers like Armistead and Kiely, (2003); Gelade and Young, (2005);Homburg (2009);Yee, Yeung, and Cheng, (2011);Williams and Naumann, (2011);; Kanyurhi (2013) tested S-PC's links in different industries, at different locations and found close association among SPC's variables. Therefore, based on results and comparison of regression results (R 2 and ANOVA) of three tiers, it is found that the values of R 2 for the entire variables are positive and significant, which shows that the results are in line with assumptions.…”
Section: Comparing Regression Results (R2 and Anova) Of The Three Tiers'mentioning
confidence: 99%
“…Bergami and Bagozzi (2000) follow this argumentation and define the identification with an organization "as a form of social identification whereby a person comes to view him-or herself as a member of a particular social entity, the organization" (Bergami/Bagozzi, 2000, p. 557). This definition encloses both the identification of an employee or member with its organization, as well as the identification of consumers with a company (Homburg et al, 2009). The identification of the customer with a company is referred to as customer-company identification (CCI).…”
Section: Identification With Brandsmentioning
confidence: 99%